2022
DOI: 10.1177/17588359221096219
|View full text |Cite
|
Sign up to set email alerts
|

Immune escape mechanisms and therapeutic approaches in cancer: the cancer-immunity cycle

Abstract: The introduction of immune checkpoint inhibitors has changed the therapeutic possibilities for various cancer types. However, despite the success in some entities, a significant fraction of patients does not respond to immune checkpoint inhibitors. A functioning cancer-immunity cycle is needed as the precondition for a clinically meaningful response to immune checkpoint inhibitors. It is assumed that only if each step of the cycle is activated and functioning properly, immune checkpoint inhibitors induce a mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 123 publications
0
15
0
Order By: Relevance
“…Despite the clinical success of antibodies against immunomodulators such as PD‐L1/PD‐1 and CTLA4, only a small fraction of individuals have a lasting benefit, suggesting the urgency of an efficient cancer‐immunity cycle to iteratively proceed and expand, and thus generate anticancer immune responses 28,29 . Our research revealed that GNG4 may be involved in the initiation of several key steps in the cancer immune cycle.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Despite the clinical success of antibodies against immunomodulators such as PD‐L1/PD‐1 and CTLA4, only a small fraction of individuals have a lasting benefit, suggesting the urgency of an efficient cancer‐immunity cycle to iteratively proceed and expand, and thus generate anticancer immune responses 28,29 . Our research revealed that GNG4 may be involved in the initiation of several key steps in the cancer immune cycle.…”
Section: Discussionmentioning
confidence: 88%
“…The MYC oncogene is a grand orchestrator of cancer growth and immune evasion, and it can regulate the TME by affecting both innate and adaptive immune effector cells and immune regulatory cytokines 32,33 . Relating to immune infiltration, E2Fs are potential biomarkers for prognosis of many cancers, including human gastric carcinoma, pancreatic adenocarcinoma and clear cell renal cell carcinoma 24–36 . In addition, low expression of GNG4 was associated with enrichment in the TNF‐γ and INF‐α signalling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Immune system is the “scavenger” in the body. In cancer patients, impaired cancer immune circulation leads to anti-tumor immune deficiency, which is also the cause of cancer occurrence and development ( Starzer et al, 2022 ). We found that ssGSEA scores of HLA, CD8+ T cells, T helper cells and B cells in low-risk group were noticeably higher than in high-risk group.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the cancer‐immunity cycle involves several steps to initiate an effective T‐cell‐mediated immune response, including antigen release from the necrotic or apoptotic tumor cells, antigen uptake by antigen‐presenting cells (APCs) and presentation on major histocompatibility complex class (MHC), antigen presentation to naïve T cells in the draining lymph node, activated tumor‐specific cytotoxic T lymphocytes (CTLs) infiltrate the local tumor site, effector T cells kill cancer cells, and the release of additional cancer antigens. [ 28 ] Only when each step of the cycle is activated, an effective immune response can be induced. However, M2‐polarized macrophages, myeloid‐derived suppressor cells (MDSCs), Tregs, and immune‐suppressive molecules on tumor cells and T cells enable the tumor to evade the anticancer immune response.…”
Section: Cancer Immunotherapymentioning
confidence: 99%